VAR : atualizações disposicionais durante a Copa do Mundo FIFA 2018 - Leonardo José de Lima Melgaço (2020)
The aim of this dissertation is to map VAR’s implementation and emergence as a technological artifact in the FIFA World Cup 2018 based on three dispositional dimensions: FIFA World Cup mega event, 2018 FIFA World Cup media dispositif and ‘topics of interest’ on the Twitter platform. In other words, we engage in a discussion based on empirical exercises about strategic updates linked to the technopolitical artifact Video Assistant Referee (VAR) before and during the most profitable and larger audience football championship. Strongly inspired by the notion of “dispositif” proposed by Michel Foucault and by commentators, the dissertation discusses the installation of VAR as a strategic urgency for maintaining a power game. Additionally, this perspective emphasizes this composition by contingent heterogeneous forces that, resulting of the clashes between the interests of the designers and their possibilities of appropriation, it is marked by uncertainties and by its media positivity. The work is also anchored in authors and methods linked to the interfaces between communication and media studies and Science and Technology Studies (STS). In chapter 2 we described the ‘program of action’ of the technopolitical artifact VAR, with special interest in the strategies of the protagonists (FIFA, above all) and in the distribution of skills imbued in the technology of revision in football. Then, we unveiled the VAR’s infrastructural dimension and its integration with the FIFA’s World Cup 2018 media dispositif, based on the patent for video technology and its television transmission protocol. In chapter 3, we identified the “topics of interest” associated with the performance of VAR during the hosting of the FIFA World Cup 2018 by Portuguese-speaking fans on Twitter. To discuss the emergence of VAR on this platform, we shifted our gaze to the materially traceable dispositional arrangements through a set of posts collected through the Twitter Streaming API. In dialogue with the proposal of digital methods, we identified, from the co-occurrence of words used in the tweets, five topics of interest that point out creative and pedagogical appropriations about the video referee.